The resistance of succedaneous teeth to periapical infection: A series of seven cases - Paul Chalakkal; Neil De Souza; Ida de Noronha de Ataide; Francis Akkara; Roshni Chandran (Wolters Kluwer Medknow Publications, 2021)
Pediatric dental procedures are carried out largely to prevent the adverse effects of primary teeth infection on succedaneous teeth (ST). The existing literature on how and when periapical infection (PI) from primary teeth affect ST is conflicted. A series of seven case reports on PI (abscesses and radicular cysts) from primary molars, until the eruption of the premolars, have been illustrated. The resistance of ST to PI based on their developmental stages is also discussed.